Inpauema, a new genus of Odiniidae (Diptera) from Brazil, with description of five new species - Limeira-De-Oliveira, Francisco; Marques, Dayse W. A.; Reis, Geniana A.; Rafael, José A. (Zootaxa, 2017)
A new genus and five new species of odiniids (Odiniidae: Traginopinae) are described from the Brazilian Amazon and Cerrado biomes: Inpauema mirador gen. nov. et sp. nov. (type species), I. catarinae sp. nov., I. gaimarii sp. nov., I. raimundoluizi sp. nov., and I. xavieri sp. nov. The genus is being characterized by a unique combination of diagnostic characters: body predominantly dark brown to black, with silvery-gray pruinose spots on inner margin of eyes, longitudinally along middle of lunule and face, on notopleuron and mesopleuron; postcranium concave from dorsal view; one pair of stout proclinate ocellar setae; postocellar setae absent; lunule shorter than frons; gena lacking upturned seta; antennae separated by a maximum distance of 2X the diameter of a single antennal socket and gonocoxal apodemes directed upward, forming an arch. A key to separate Helgreelia Gaimari, 2007 from Inpauema gen. nov. and for the new species is provided.